2018
DOI: 10.1007/s11250-018-1680-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of subclinical hypocalcemia in dairy cows in the Sousa city micro-region, Paraíba state

Abstract: Subclinical hypocalcemia is a metabolic disorder characterised by a decrease in serum calcium (Ca) levels, with no clinical symptoms. The aim of this study was to determine the punctual prevalence of subclinical hypocalcemia in dairy cows, in the Sousa city micro-region, Paraíba state. Samples were collected from 29 dairy farms, consisting of 153 and 296 blood samples in the pre- and postpartum period respectively. In relation to the mineral supplementation profile, 89.25% of the properties use a commercial su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…As intravenous 22.5% calcium borogluconate infusion immediately induces a state of hypercalcemia, followed by reduction of the whole blood ionized calcium (iCa) and serum total calcium (tCa) concentrations 24 hr later [ 28 ]. Therefore, it is difficult to maintain an ideal blood calcium level without monitoring the blood calcium level [ 11 ].…”
mentioning
confidence: 99%
“…As intravenous 22.5% calcium borogluconate infusion immediately induces a state of hypercalcemia, followed by reduction of the whole blood ionized calcium (iCa) and serum total calcium (tCa) concentrations 24 hr later [ 28 ]. Therefore, it is difficult to maintain an ideal blood calcium level without monitoring the blood calcium level [ 11 ].…”
mentioning
confidence: 99%
“…Respecto a los valores normales de calcio en las vacas adultas, la literatura reporta una gran variabilidad, encontrándose resultados de 8,5 a 10 mg/dL (Goff, 2008), ≥8,9 a 11,0 mg/dL (Herdt et al, 2000), 10 a 12 mg/dL (Manual Merck de Veterinaria, 2000), entre otros; pero coincidiendo en que niveles <8m/dL y <4 mg/dL en tCa y iCa, respectivamente, son considerados como hipocalcemia (Herdt et al, 2000). De la misma forma, cuando los valores están por debajo de 5.5 mg/dL de tCa el animal comenzará a presentar signos clínicos (da Silva et al, 2019).…”
Section: Hipocalcemiaunclassified
“…Muchos de los problemas descritos anteriormente pueden presentarse en la SCH. Por esta razón es importante como medida diagnóstica realizar mediciones de los niveles de Ca (da Silva et al, 2019;Van Saun, 2016) en el periodo de estrés metabólico, es decir, antes del parto y después para identificar vacas que presentarán problemas (Van Saun, 1997). Al no estar familiarizados con métodos rentables (económicos y efectivos) para la medición de Ca en campo, suele ser imposible saber si la aplicación del Ca al postparto es usado como tratamiento preventivo o curativo de la enfermedad (McArt & Oetzel, 2015).…”
Section: Hipocalcemiaunclassified
“…Many studies have reported that subclinical hypocalcemia occurs in almost half of the cows depending on parity in dairy herds (Jawor et al, 2012;Neves et al, 2018;Da Silva et al, 2019). Subclinical hypocalcemia impairs the metabolic and physiological responses that regulate the welfare and productivity of transitional dairy cows (Rodrigues et al, 2020).…”
Section: Introductionmentioning
confidence: 99%